2014
DOI: 10.1007/s00125-014-3388-4
|View full text |Cite
|
Sign up to set email alerts
|

The adverse association of diabetes with risk of first acute myocardial infarction is modified by physical activity and body mass index: prospective data from the HUNT Study, Norway

Abstract: Aims/hypothesis Diabetes increases the risk of acute myocardial infarction (AMI) and effective means for primary prevention are warranted. We prospectively examined the joint association of diabetes and leisure-time physical activity, as well as of diabetes and BMI, with the risk of AMI. Methods A total of 55,534 men and women in the Norwegian HUNT Study were followed-up for first AMI by hospital admission registries and the Cause of Death Registry. Cox proportional adjusted HRs with 95% CIs were estimated. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…By damaging vascular function, DM paves the way for the development of atherosclerosis and doubles the risk of AMI. [ 39 ] It seems that daily consumption and number of cigarette packs per year are associated with progression of impaired fasting glucose and type 2 diabetes as well as metabolic syndrome. [ 40 ] A decreased incidence of hospitalization for AMI is associated with smoking ban.…”
Section: Discussionmentioning
confidence: 99%
“…By damaging vascular function, DM paves the way for the development of atherosclerosis and doubles the risk of AMI. [ 39 ] It seems that daily consumption and number of cigarette packs per year are associated with progression of impaired fasting glucose and type 2 diabetes as well as metabolic syndrome. [ 40 ] A decreased incidence of hospitalization for AMI is associated with smoking ban.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity is important for disease management in patients with type 1 diabetes (23) and a recent study demonstrated that physical activity modifies the risk of first acute myocardial infarction in these patients (19). Furthermore, physical activity is protective against the development of type 2 diabetes (15).…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity has been suggested as a key lifestyle strategy for the prevention and management of diabetes mellitus because of its beneficial effects on cardiometabolic profiles and mortality among adults who have diabetes mellitus and who are at high risk for developing diabetes mellitus. [5][6][7] Emerging evidence suggests that longer duration of time spent in sedentary behaviors is associated with increased risk of adverse health outcomes, including type 2 diabetes mellitus, CVD, cancer, and death, independent of physical activity. 8 Recently, we reported data from a large US Hispanic/Latino cohort, the Hispanic Community Health Study/Study of Latinos (HCHS/SOL), suggesting that both sedentary behavior and moderate-to-vigorous physical activity (MVPA) have independent associations with cardiometabolic biomarkers.…”
mentioning
confidence: 99%